Penerapan Metode ARAS dan ROC dalam Menentukan Destinasi Wisata Syar’i di Kabupaten Langkat - Sari, Anggy Permata; Irawan, Muhammad Dedi (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
The growing interest in Islamic tourism has prompted the need for a system capable of accurately recommending sharia-compliant tourism destinations. Langkat Regency boasts a variety of attractive destinations, but tourists often struggle to make informed choices due to limited information, while the Tourism Office faces challenges in prioritizing destinations. This study integrates the Rank Order Centroid and Additive Ratio Assessment methods into a decision support system. ROC was used to weight eight assessment criteria based on priority, while ARAS was applied to calculate utility values and rank ten alternative destinations. The analysis showed that Taman Wisata Syariah obtained the highest utility value of 1. Thus, Taman Wisata Syariah is recommended as a prime sharia-compliant tourism destination in Langkat Regency. The integration of the ROC and ARAS methods proved effective in producing consistent, measurable evaluations, and was able to account for variations in weighting between criteria. The developed system not only improves the efficiency of the decision-making process but also provides practical contributions to the management and development of sustainable sharia tourism in Langkat Regency.